A política de crescimento econômico e a felicidade no projeto societário capitalista: uma análise contemporânea - CAMEJO, Maria Soledad (2023)
This thesis addresses the relationship between happiness and the economic factors that circumscribe our lives with a view to a critical analysis of economic growth policy. Happiness is understood as a state of self-perception that is approached from the scientific concepts of subjective well-being and self-actualization. It starts from the understanding that although it has an individual expression and a unique constitution in each of us, it is incomprehensible until the molds in which it emerges as a human value are referenced and in this sense the public dimension of happiness and the government actions to materialize it. Happiness can be thought of as a social project and above all as the source that legitimizes the policy of economic growth. The fundamental question that is of particular interest in the proposed research is to elucidate to what extent, from the accumulation of current scientific research, the observations, very especially developed by Marx, on the intrinsic problematic of the capitalist system that has to do with the fact that that material production, and even the production of life, are subsumed at the service of capital accumulation and not at the service of human needs. The most elementary question that involves this thesis is precisely why it is unquestionable to grow from the point of view of happiness. Based on a Marxist perspective and a methodological strategy based on Bibliographic Research, the thesis indicates more than a blatant doubt, the fanciful illusion that involves the policy of economic growth as a way to achieve greater levels of satisfaction. What can be deduced in this sense from the surveys consulted is that in the face of growing production, from the point of view of the targets of the economic growth policy, everything indicates that it will be possible to continue adding the available goods, but this may only be a endless rush and with little fruit for the population over time. Capitalism is a machine for producing more desires, more expectations and more drive for a better future, and the policy of economic growth is the most strongly established tribute in this sense.